The impact of a 5G-based smart nursing information system and associated mobile hardware on clinical nurses’ work stress: a randomized controlled study in a Chinese hospital - Xuejiao Ruan; Yuying Lou; Xinhua Zhang; Zhulin Wu; Hongzhi Yuan (BioMedical Engineering OnLine)
Abstract Background Clinical nurses frequently endure substantial work-related stress, adversely affecting their well-being and potentially compromising patient care quality and safety. The integration of a 5G-based medical private network into smart nursing systems and mobile devices offers a promising solution to reduce this stress. This study evaluates the impact of a Smart Nursing Information System based on a 5G Medical Private Network and its Supporting Mobile Hardware (SNIS-SMH) on mitigating work-related stress among clinical nurses. The goal is to provide a scientific basis for nursing management, reduce error incidents, advance nursing procedures, and enhance productivity. Results A total of 226 nurses completed the study. The SNIS-SMH group showed significantly lower total work stress scores (66.16 ± 9.82) compared to the control group (70.65 ± 11.32, P = 0.002). In specific dimensions, the SNIS-SMH group had lower scores for nursing profession and work (14.17 ± 2.37 vs. 15.00 ± 3.06, P = 0.023), workload and time distribution (10.56 ± 2.45 vs. 12.42 ± 2.55, P < 0.001), and patient care (22.55 ± 3.34 vs. 23.70 ± 4.06, P = 0.021). No significant differences were found in the work environment and resource, and management and interpersonal relationships dimensions. Conclusions The SNIS-SMH system significantly alleviated work-related stress among clinical nurses, particularly in nursing duties, workload and time distribution, and patient care.